Predictors of Septic Shock or Bacteremia in Children Experiencing Febrile Neutropenia Post-Chemotherapy. Issue 11 (4th August 2022) - Avilés-Robles, Martha; Schnur, Jennifer J; Dorantes-Acosta, Elisa; Márquez-González, Horacio; Ocampo-Ramírez, Luis A; Chawla, Nitesh V
Abstract: Background: Febrile neutropenia (FN) is an early indicator of infection in oncology patients post-chemotherapy. We aimed to determine clinical predictors of septic shock and/or bacteremia in pediatric cancer patients experiencing FN and to create a model that classifies patients as low-risk for these outcomes. Methods: This is a retrospective analysis with clinical data of a cohort of pediatric oncology patients admitted during July 2015 to September 2017 with FN. One FN episode per patient was randomly selected. Statistical analyses include distribution analysis, hypothesis testing, and multivariate logistic regression to determine clinical feature association with outcomes. Results: A total of 865 episodes of FN occurred in 429 subjects. In the 404 sampled episodes that were analyzed, 20.8% experienced outcomes of septic shock and/or bacteremia. Gram-negative bacteria count for 70% of bacteremias. Features with statistically significant influence in predicting these outcomes were hematological malignancy ( P < .001), cancer relapse ( P = .011), platelet count ( P = .004), and age ( P = .023). The multivariate logistic regression model achieves AUROC = 0.66 (95% CI 0.56–0.76). The optimal classification threshold achieves sensitivity = 0.96, specificity = 0.33, PPV = 0.40, and NPV = 0.95. Conclusions: This model, based on simple clinical variables, can be used to identify patients at low-risk of septic shock and/or bacteremia. The model's NPV of 95% satisfies the priority to avoid discharging patients at high-risk for adverse infection outcomes. The model will require further validation on a prospective population. Abstract : This study performs univariate and multivariate analysis using simple clinical variables to identify pediatric oncology patients at low-risk for septic shock and/or bacteremia outcomes.